Reflexões sobre a medicalização na saúde mental : um ensaio do fenômeno na saúde e na atenção psicossocial - Sá, Dalmare Anderson Bezerra de Oliveira (2017)
This dissertation aims at reflecting, from a historical-conceptual theoretical framework of medicalization and history of mental health care, how this phenomenon has advanced as part of general health care, also represented by the growth of population use of medication, particularly about the psychopathologies and mental health care in our society, at last the paper performs an analysis of practices and actions of mental health care at a psychosocial attention network, infering how much the medicalizing and de-medicalizing practice is present in the services and care provided, also evaluating how much the phenomenon is harmful/beneficial to practices and care in health. This work is characterized by being a bibliographical review of seminal articles, mainly focused on national authors, being characterized as a strategic health research.The conceptual framework of medicalization goes from the most orthodox criticism to the imperial power of medicine over lives, through Foucault's concept about the process of medicalization being part of the building of State as we know it, until even contemporary thinkers who study the process of de-medicalization and quaternary prevention in health. The mental health care historical investigation shows us how psychopathologies stand out of the socialaté exclusion as a model of psychiatry and mental health care free and was reinserted into the community, being this the brazilian bet originated from the Democratic Italian Psychiatry purpose, having Franco Basaglia as its biggest mentor. We move then to an analysis of how the process of medicalization influences health in general with a quantitative perspective to the growth in the use of medication and qualitative to the amplification of what is disorder and mental illness, to a more detailed analysis of how intrinsic health actions and practices are medicalizing. A final positive aspect of this paper is to always look for an analysis of how much the processes of medicalization and society's loss of autonomy can be broken, also considering that for some health conditions the advance of the biomedic view to care was very important. As a conclusion, this study points to the positive aspects of medicalization, the need for greater exploitation of mental health care, the potential for building autonomy that it brings, and that the pharmaceutical sciences have much to contribute in this field of knowledge.